| **Giver** | **Post** | **Date** |

| SPEEDBOATS | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 28-Sep-2023 |

| 52010078 | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 22-Aug-2023 |

| tranthanhbinh | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 02-Sep-2021 |

| abhimanyujain1711 | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 03-Jul-2021 |

| 1610ayush | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 16-Nov-2020 |

| awichal | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 24-Aug-2020 |

| GMATSheep | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 28-Mar-2020 |

| NYDukie | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 11-Sep-2019 |

| attempttoo | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 12-May-2019 |

| alexiszecua | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 26-Mar-2019 |

| robertaconte | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 13-Nov-2018 |

| peterpark | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 13-May-2018 |

| TESCHNL | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 07-Apr-2018 |

| bingzhang | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 04-Feb-2018 |

| gmatinsead2018 | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 06-Jan-2018 |

| Divya17 | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 19-Oct-2017 |

| Varun121595 | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 07-Oct-2017 |

| thangvietnam | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 21-Jul-2017 |

| Bjoerngo | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 06-Mar-2017 |

| dpgiii | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 29-Jul-2016 |

| Fifi | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 26-May-2016 |

| aarontschmidt | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 10-May-2016 |

| tudelue | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 12-Apr-2016 |

| shasadou | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 22-Jan-2016 |

| kls1511 | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 16-Dec-2015 |

| shahrukhtauqir | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 14-Nov-2015 |

| katarinak | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 10-Nov-2015 |

| burgeoning | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 31-Aug-2015 |

| reto | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 10-May-2015 |

| gmattgmattt | Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 30-Mar-2015 |